Illegal Pawn Practices Amid the Covid-19 Pandemic To Survive (Journal of Private and Commercial Law, 2021)
This article aims to explain illegal pawning in the midst of the Covid-19 pandemic in Indonesia, this pandemic has caused losses to the economic sector and almost all sectors are affected by activity restrictions which increasingly make people unable to run their businesses so that some have to lose their jobs and cannot support them. their family. This August report from the Central Statistics Agency (BPS) stated that Indonesia's economic growth in the second quarter of 2020 was minus 5.32 percent. With this difficult situation some people choose to pawn their goods or assets to illegal plaintiffs, people who are easily affected because of the easy and fast process tend to prefer private pawns that do not have this permit compared to official pawns that have been registered with the OJK.Â Keywords : Pawn; Law; Loan;